2005
DOI: 10.1093/toxsci/kfi250
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Development of a Predictive Paradigm for Hemotoxicology Using a Multifunctional Bioluminescence Colony-Forming Proliferation Assay

Abstract: The lympho-hematopoietic colony-forming assay has been redesigned into a rapid, nonsubjective and standardized proliferation assay that can measure the effects of compounds on multiple stem and progenitor cell populations from different species simultaneously using a sensitive, high-throughput bioluminescence readout. Eleven reference compounds from the Registry of Cytotoxicity (RC) and eight other compounds, including anticancer drugs, were studied over an 8- to 9-log dose range for their effects on seven cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…31 Other tests of hematopoietic potency have been proposed, the expression of aldehyde dehydrogenase by MNCs 32 and the levels of ATP after culture in the presence of selective cytokine cocktails. 33 Information on the clinical relevance of these reasonably putative markers is still preliminary.…”
Section: Collected Cord Blood: Cells and Hematopoietic Potencymentioning
confidence: 99%
“…31 Other tests of hematopoietic potency have been proposed, the expression of aldehyde dehydrogenase by MNCs 32 and the levels of ATP after culture in the presence of selective cytokine cocktails. 33 Information on the clinical relevance of these reasonably putative markers is still preliminary.…”
Section: Collected Cord Blood: Cells and Hematopoietic Potencymentioning
confidence: 99%
“…Assay standardization also allows results to be compared over time, a property that is especially important in establishing reference standards within and between laboratories. This readout technology has been incorporated into a stem cell quality assay [13] and two potency assays, one developed for lympho-hematopoietic cells (HALO-96 PQR) and one for mesenchymal stem/stromal cells (LUMENESC-96 PQR). Both assays use the same concepts and principles described here to measure potency and quality and defining acceptance limits for releasing the product for use [14,15].…”
Section: Assay Readoutmentioning
confidence: 99%
“…Prior to measuring bioluminescence of the samples after culture incubation, an ATP standard curve was performed (Rich & Hall, 2005;Reems et al 2008;Hall & Rich, 2009). Serial dilutions from a 10M stock concentration were prepared so that the final dilutions were 5, 1, 0.5, 0.1, 0.05, 0.01 and 0.005M.…”
Section: Assay Calibration Standardization and Sample Processingmentioning
confidence: 99%
“…It had been previously demonstrated that when hematopoietic stem cells were stimulated to proliferate in the presence of growth factors and cytokines, the intracellular ATP (iATP) concentration increased proportionately to the cell concentration plated (Rich & Hall, 2005;Rich, 2007). The steepness or slope of the cell dose response was dependent upon the primitiveness and proliferation potential of the cells being examined.…”
Section: Introductionmentioning
confidence: 99%